PENGARUH PEMBELAJARAN ILMU FIQH DALAM PERSPEKTIF KESEHATAN REPRODUKSI - Ahmad Edwar (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
Based on the educational problems in Indonesia today which are considered increasingly complex, the author seeks to study the learning of fiqh based on reproductive health. In the implementation of this study using a literature approach with descriptive analysis methods. Fiqh learning based on reproductive health is the concept of developing Fiqh material that is produced by reviewing the previous curriculum which is considered not aware of adolescent problems, especially in the context of reproductive health. Adolescent problems often stem from a lack of information and understanding and awareness of the importance of maintaining reproductive health. On the other hand, adolescents themselves experience rapid physical changes. There must be a shared belief that building a next generation of quality needs to start from the child, even from the womb. The concept of reproductive health-based fiqh learning is an offer for the development of madrasah aliyah fiqh subjects related to certain themes related to reproductive health, such as material, adultery, iddah and others.